Center volume and primary graft dysfunction in patients undergoing lung transplantation in the United States – a cohort study. (28th November 2020) - Jawitz, Oliver K.; Raman, Vignesh; Bryner, Benjamin S.; Klapper, Jacob; Hartwig, Matthew G.
Summary: Lung transplantation primary graft dysfunction (PGD) is common and portends poor outcomes. We examined the association of lung transplant center volume with PGD and the risk of mortality. The United Network for Organ Sharing transplant registry was queried for adult lung transplants from March 2015 to March 2019. Recipients were stratified by the occurrence of grade 3 PGD 72 h post‐transplant, defined using modified ISHLT criteria. The adjusted association between volume and PGD as well as post‐PGD survival was analyzed. 7322 recipients were included, among whom approximately 21% ( n = 1525) experienced grade 3 PGD. After adjustment, increasing annualized lung transplant volume was associated with a decrease in the odds of PGD in a near‐linear fashion (OR 0.94 per 10 transplants, 95% CI 0.89–0.99). Furthermore, increasing annualized lung transplant center volume up to approximately 55 transplants per year was associated with improved survival among patients with grade 3 PGD (HR 0.87 per 10 transplants, 95% CI 0.79–0.94). Increasing annual lung transplant center volume is associated with a decreased incidence of grade 3 PGD. Further, increasing volume among low‐ and medium‐volume centers is associated with improved survival of patients who experience PGD.